A study of acoustic emission properties on welded A240GR 317L stainless steel using acoustic amission transmission under tensile load - Muhammad Shahmi, Marsahid (2012)
This project presented the study on AE properties of welded A240GR 317L stainless steel using Acoustic Emission Testing (AET) under tensile load. This project were involving three main objectives which is to acquire acoustic emission (AE) data from tensile test on base metal and welded specimens and also to analyze AE properties and find the correlation to the stress-strain curve. Tensile test were used to make the cracks propagation and to analyze the properties based on stress strain curve. There is two condition prepared for the tensile test which base metal specimen and welded specimen. AE piezoelectric sensor were used to detects AE activities during tensile test been conducted. The AE data acquired being selected in number of 30 samples by comparing the waveform for each data. Then it was plotted in Stress and AE properties versus time to get the correlation of tensile activity with AE properties. Results show that the AE activity is high during elastic region before the tensile strength, and it is reduced significantly with respected to the nominal strain and increased back in plastic region until fracture. AE properties were recorded more in welded specimen compared to the base metal because of the defect of welding. Kaiser effect is happened because of the significant reduced of load after tensile strength causing by the dislocation of structure from elastic to plastic region. Acoustic emission technique is widely used in industry to as a condition monitoring technique to monitor the equipments such as pipes and pressure vessels condition.